Impact of biological sex, concussion history and sport on baseline NeuroTracker performance in university varsity athletes - Acquin, Jean-Michel; Desjardins, Yannick; Deschamps, Alexandre; Fallu, Étienne; Fait, Philippe; Corbin-Berrigan, Laurie-Ann (Frontiers in Sports and Active Living, 2024)
This study aimed to assess the impact of biological sex, concussion history, and type of sport on the baseline NeuroTracker performance, a test/train three-dimensional multiple object tracking paradigm used in sport contexts, in university level varsity athletes. A total of 136 university level varsity athletes participating in male ice hockey, male or female soccer, female volleyball, and mixed biological sex cheerleading underwent preseason NeuroTracker baseline assessments. Significant differences in NeuroTracker performance were observed based on biological sex (p < 0.01) and type of sport played (p < 0.05). Male athletes and hockey players demonstrated higher NeuroTracker performance compared to their counterparts. However, no significant differences were found in NeuroTracker performance based on the history of concussion. Thus, factors such as biological sex and type of sport played may influence baseline NeuroTracker performance.